The Eastward Enlargement of the Eurozone Final Report on "Exchange Rate Regimes" - Renzo Orsi; Fabrizio Iacone (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
The CEEC are approaching the accession to the EU with a variety of exchange rate regimes. The authors find that these differences depend on economical factors as well as on the history of the countries. For that purpose, they discuss the role of the exchange rate in the stabilization of the inflation rate at the beginning of the transition from the central planning to the market economy, finding that, combining internal price liberalisation, openness to the international trade and a commitment to exchange rate stability the countries in transition - with the exception of Slovenia - provided the system with a nominal anchor by importing the price structure of the trade partners. Later, the capital liberalisation required for the progressive integration in the EU exposed the CEEC to speculative attacks and exchange rate pressure and most of them weakened the exchange rate commitment or withdrew it at all. The Baltic States are the only ones still maintaining a strong exchange-rate commitment. The authors conjecture that this is due to the smaller size of these countries, which makes the interest rates of the domestic currency of little importance to the economy when compared to the exchange rate. Policy advice completes this report.
Keywords: F0; E5; E0; 330; Exchange Rate Regimes for CEEC; Optimum Currency Areas; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Osteuropa